Monitoring Quality Of Soda Black Liquor Of Oil Palm Empty Fruit Bunch Fibers In Terms Of Storage Time And Temperature - Ibrahim, M. N.; Wan Rosli, W. D.; Chuah, S. B. (Penerbit UTM Press, 2005)

(untitled)
The Quality Of Black Liquor From Oil Palm Empty Fruit Bunch Fibers Pulping Was Determined Through Direct Isolation Of Soda Lignin Using 10% Hydrochloric Acid At Three Ph Fractions, I.E. Ph 2, Ph 4 And Ph 6. Destructive Methods Such As Nitrobenzene Oxidation And Ash Contents Determination Were Used In The Study. Ph 2 Was Found To Be The Most Preferable Fraction Due To The Highest Lignin Yield. Nitrobenzene Oxidation Showed That The Predominant Compound Was Vanillin, Which Was In The Range Of 44.9-52.1% Of The Total Product. Syringaldehyde Was The Second Major Compound (Ca. 21.5-30.8%), Followed By P-Hydroxybenzaldehyde. The Moisture And The Ash Contents Of Ph 6 Fraction Were The Highest Followed By Ph 4 Fraction And Ph 2 Fraction, Especially At Longer Storage Time. Soda Lignin Has To Be Isolated In Less Than 15 Days Of Storage Regardless Of Storage Temperature To Prevent High Rate Of Biodegradation Activities.